2013
DOI: 10.1002/grl.50135
|View full text |Cite
|
Sign up to set email alerts
|

Remote energetic neutral atom imaging of electric potential over a lunar magnetic anomaly

Abstract: [1] The formation of electric potential over lunar magnetized regions is essential for understanding fundamental lunar science, for understanding the lunar environment, and for planning human exploration on the Moon. A large positive electric potential was predicted and detected from single point measurements. Here, we demonstrate a remote imaging technique of electric potential mapping at the lunar surface, making use of a new concept involving hydrogen neutral atoms derived from solar wind. We apply the tech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
60
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 40 publications
14
60
0
1
Order By: Relevance
“…For a full understanding of the structure and dynamics of magnetosphere, however, a six-dimensional Vlasov simulation (with three spatial dimensions) is essential, because the topology of magnetic fields and convection pattern is modified in three spatial dimensions from those in two spatial dimensions. As the in situ observation shows, there is no bow shock above the Lunar magnetic anomaly (Futaana et al 2013), while the formation of the bow shock is confirmed in the present global simulation with two spatial dimensions. The full six-dimensional global Vlasov simulation is left as a far future study, since it would require massive computing resources beyond Exascale.…”
Section: Resultssupporting
confidence: 79%
“…For a full understanding of the structure and dynamics of magnetosphere, however, a six-dimensional Vlasov simulation (with three spatial dimensions) is essential, because the topology of magnetic fields and convection pattern is modified in three spatial dimensions from those in two spatial dimensions. As the in situ observation shows, there is no bow shock above the Lunar magnetic anomaly (Futaana et al 2013), while the formation of the bow shock is confirmed in the present global simulation with two spatial dimensions. The full six-dimensional global Vlasov simulation is left as a far future study, since it would require massive computing resources beyond Exascale.…”
Section: Resultssupporting
confidence: 79%
“…A complicated magnetic footprint that is limited in extent and isolated was observed by the SARA instument on Chandrayaan-1 Vorburger et al 2012;Futaana et al 2013) (at  22 S and  240 E on the lunar far side, and shown in the left two panels of Figure 6). Such a structure would appear in the far-field as a single dipole, similar to that used in the simulation (shown in the right panels of Figure 6).…”
Section: Comparison With Lunar Swirlsmentioning
confidence: 94%
“…Energetic neutral atom (ENA) imaging of the Moon from Chandrayaan‐1 observations showed that a partial void of the solar wind plasma, a minimagnetosphere, forms above one of the strongest lunar magnetic anomalies located at the Crisium antipode near the Gerasimovich crater, known as Gerasimovich magnetic anomaly [ Wieser et al , ; Vorburger et al , ; Futaana et al , ]. They showed that the ENA flux was substantially reduced above the magnetic anomalies, while it was increased in the surrounding regions, indicating plasma deflection around crustal fields.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the ENA flux was substantially reduced above the magnetic anomalies, while it was increased in the surrounding regions, indicating plasma deflection around crustal fields. By studying the energy spectrum of the ENA population, they estimated an electrostatic potential of larger than +135 V inside the Gerasimovich magnetic anomaly [ Futaana et al , ]. They also found that the Gerasimovich magnetic anomaly possesses a clearer correlation between the incident plasma parameters and the surface shielding efficiency compared to the other crustal fields, which is presumably due to its simple magnetic field topology compared to the other crustal fields, especially compared to the South Pole‐Aitken basin region [ Vorburger et al , ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation